A New Reversible Thermosensitive Liquid–Solid TENG Based on a P(NIPAM‐MMA) Copolymer for Triboelectricity Regulation and Temperature Monitoring. Issue 21 (29th April 2022) - Feng, Min; Kong, Xiang; Feng, Yange; Li, Xiaojuan; Luo, Ning; Zhang, Liqiang; Du, Changhe; Wang, Daoai
Abstract: Intelligent and highly precise control of liquid–solid triboelectricity is of great significance for energy collection and electrostatic prevention. However, most of the traditional methods are irreversible and complex, greatly limiting their applicability. Here, a reversible thermosensitive liquid–solid triboelectric nanogenerator (L–S TENG) is assembled based on P(NIPAM‐MMA) (PNM) copolymer for tunable triboelectrification. Through temperature regulation, the conformation between acylamino and isopropyl groups changes with the interfacial wettability and triboelectricity of PNM. When the temperature rises from 20 to 60 °C, the contact angle of PNM rises from 22.49° to 82.08°, and the output of the PNM‐based L–S TENG shows a 27‐fold increase. In addition, this transformation is reversible and repeatable with excellent durability for up to 60 days. Other organic liquids, such as glycol, exhibit positive response to temperature for this PNM‐based L–S TENG. Polymers including polymethylmethacrylic, polytetrafluoroethylene, and polyimide are verified to not have such thermo‐sensitivity properties. In addition, a droplet‐based wireless warning system based on PNM is designed and actuated for monitoring specific temperature. The introduction of thermal PNM not only provides new material for reversible manipulation of L–S TENG, but also provides a new method for designing highly sensitive temperature warning sensors. Abstract : In this work, a thermosensitive P(NIPAM‐MMA) based liquid–solid triboelectric nanogenerator (PNM‐based L–S TENG) is developed through free radical polymerization and spin‐coating. From 20 to 60 °C, the outputs of the PNM‐based L–S TENG show a 27‐fold increase. Wettability and triboelectric change under temperature control are reversible. A PNM‐based wireless warning sensor is demonstrated to monitor specific temperature.